1988
DOI: 10.1042/bj2550937
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of pentagalloylglucose, and α-glucosidase inhibitor/antibiotic from the freshwater green alga Spirogyra varians

Abstract: An alpha-glucosidase inhibitor/antibiotic was purified from the freshwater green alga Spirogyra varians and was determined to be the pentagalloylglucose 3-O-digalloyl-1,2,6-trigalloylglucose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

1989
1989
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 10 publications
0
28
0
1
Order By: Relevance
“…Kinetic studies indicated that PGG was a mixed-type inhibitor of FabG with respect to NADPH. In another study, Cannell et al isolated a isomer of PGG, 3- O -digalloyl- 1,2,6-trigalloylglucose, from the freshwater green alga Spirogyra varians , and found that this compound irreversibly inhibited α-glucosidase and was more potent than PGG, 1 ,2, 3, 6-Tetra- O -galloylglucose or 1 ,2, 6-Tri- O -galloylglucose (75). The PGG isomer was proposed as the antibacterial agent in the methanol extract of Spirogyra varians .…”
Section: Other Biological Activitiesmentioning
confidence: 99%
“…Kinetic studies indicated that PGG was a mixed-type inhibitor of FabG with respect to NADPH. In another study, Cannell et al isolated a isomer of PGG, 3- O -digalloyl- 1,2,6-trigalloylglucose, from the freshwater green alga Spirogyra varians , and found that this compound irreversibly inhibited α-glucosidase and was more potent than PGG, 1 ,2, 3, 6-Tetra- O -galloylglucose or 1 ,2, 6-Tri- O -galloylglucose (75). The PGG isomer was proposed as the antibacterial agent in the methanol extract of Spirogyra varians .…”
Section: Other Biological Activitiesmentioning
confidence: 99%
“…This includes the genus Rhus, Schinus, Galla, Paeoniae Radix (the root of Paeonia lactiflora Pallas), Moutan cortex (the root cortex of Paeonia suffruicos), Macaranga tanariu, Quercus pedunculata, peony, and green alga Spirogyra varians. 5GG has been found to have various biological activities; it inhibits lipopolysaccharide-stimulated tumor necrosis factor-␣ secretion (22), gastric H ϩ ,K ϩ -ATPase (23), NADH dehydrogenase I/II (24 -27), xanthine oxidase (28), and ␣-glucosidase (29). 5GG also exhibits an endothelium-dependent vasodilator effect on isolated rat aorta (30) and manifests an anticonvulsant action (31).…”
mentioning
confidence: 99%
“…PGG, being a tannic acid, was first isolated and purified from the freshwater green alga Spirogyra varians or a Paraguayan crude drug, bMolle-iQ (Schinus terebinthifolius) [13,14], and it has also been synthesized [15]. It is reported to be a xanthine oxidase inhibitor and to exert an effect on mitochondrial respiration and oxidative phosphorylation through action on the membrane and on succinate dehydrogenase, NADH dehydrogenase and on the cytochrome c complex of mitochondria [14,16].…”
Section: Discussionmentioning
confidence: 98%